What we talk about when we talk about cybersecurity: security in internet governance debates - Josephine Wolff (Internet Policy Review, 2016)
At meetings of internet governance organisations, participants generally agree that improving security is an important goal, but these conversations rarely yield consensus around how to achieve this outcome. One reason security plays this paradoxical role—as both a universal point of agreement and a continued source of contention—in these debates is that it has significantly different meanings to different stakeholders involved in these governance forums. In this paper, we discuss how different stakeholders define and frame internet security issues in the context of governance debates and analyse how these conflicting notions of security continue to shape emerging controversies.
Keywords: 300; Cybersecurity; Internet governance; Internet Corporation for Assigned Names and Numbers (ICANN); WCIT